Prevalencia de enfermedad periodontal en adultos indígenas Yukpa asentados en El Escobal - Cúcuta (2024)
The present study addresses the prevalence of periodontal disease in the Yukpa indigenous community settled in the city of Cúcuta, in accordance with the ethnic and cultural rights recognized by the Political Constitution of 1991. The research arises from the need to understand the oral health of this population, whose oral hygiene habits and access to health services are poorly documented. The problem focuses on the lack of information about the factors that influence the oral health of the Yukpa community, as well as the scarcity of preventive measures adapted to their cultural and socioeconomic context.